Pendampingan Peningkatan Kapasitas Produksi dan Pemasaran melalui Pembentukan Ekosistem Wirausaha Berbasis Komunitas untuk Pengembangan Kedai Gumarang - Virtuous Setyaka; Eli Ratni; Muhammad Idris; Edita Elda (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
Assistance for empowerment by increasing production and marketing capacity through establishing a community-based business ecosystem is carried out to develop Kedai Gumarang. It has been operating on Sungai Balang, Cupak Tangah Village, Pauh District, Padang City, and West Sumatra Province. Kedai Gumarang is a coffee-based beverage shop that serves the needs of urban youth as a place to interact in various activities while enjoying brewing coffee. The problem experienced by the manager of Kedai Gumarang so far is the production and marketing capacity that must be increased. The solution offered was to increase production and marketing capacity with an improved management approach through business planning based on a business model canvas (BMC) and focusing on establishing a community-based business ecosystem. The entrepreneur ecosystem was formed by bringing together creative entrepreneurs in the city of Padang based on art, books, and cafes as a space for learning and working together. The methods included brainstorming, upgrading entrepreneurial mindsets, formulating BMC, licensing assistance, and periodic monitoring and evaluation.